Professional Identity Development of Black Doctoral Students in Counselor Education: A Reflexive Model - Olivia T Ngadjui PhD; Elizabeth A. Doughty Horn (Teaching and Supervision in Counseling, 2024)
This grounded theory study comprised the perspectives of how past and current Black doctoral students formalized their professional identity in counselor education. Findings included reflexivity as a central theme within the internal process of Black doctoral students navigating counselor education programs and a model of professional identity development.
Keywords: reflexivity; professional identity development; Black doctoral students in counselor education; counselor education